PENERAPAN MEDIA PEMBELAJARAN DENGAN PEMANFAATAN LINGKUNGAN SEKITAR SEBAGAI SUMBER BELAJAR DALAM PENGAJARAN PENDIDIKAN IPS DI SEKOLAH MENENGAH PERTAMA (Penelitian Tindakan Kelas) - Suryati, Wawat (Lembaga Penelitian STKIP PGRI Bandar Lampung, 2013)
This research was meant to describe better learning process of social science at the Junior high School. This research uses aclassroom action approach. A cycle with four activities : planning, applyng, observing and reflecting was conducted to find answers to the ploblem of why teacher did not use teaching aid optimally. The finding of this research also show that using slides in the teaching can make learning more effectively